2013
DOI: 10.1016/j.breast.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel proliferation by co-expression of endothelial nestin and Ki-67 is associated with a basal-like phenotype and aggressive features in breast cancer

Abstract: Microvessel proliferation is a novel marker of ongoing angiogenesis and was associated with aggressive tumour features, basal-like phenotypes, interval presentation, and prognosis in this series of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 29 publications
10
47
1
Order By: Relevance
“…However, only MVP reached significance among this group of patients (p=0.0001). Our results are in line with previous reports that found increased vascular proliferation in basal-like breast tumors, but using different markers of vascular proliferation (18)(19)(20). The mechanism of this association is not known, although some authors suggest that vascular endothelial growth factor (VEGF), as a regulator of angiogenesis, contributes to increased vascular proliferation in basal-like tumors (18,22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, only MVP reached significance among this group of patients (p=0.0001). Our results are in line with previous reports that found increased vascular proliferation in basal-like breast tumors, but using different markers of vascular proliferation (18)(19)(20). The mechanism of this association is not known, although some authors suggest that vascular endothelial growth factor (VEGF), as a regulator of angiogenesis, contributes to increased vascular proliferation in basal-like tumors (18,22).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that vascular proliferation is a sensitive method for evaluation of angiogenesis, with more reliable results compared with standard MVD (18)(19)(20)(21). MVP is a relatively new parameter of angiogenesis that measures the most active tumor vasculature, while MVD includes both preformed and newly formed vessels (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Fringe stabilizes tip and stalk fates and can help promote physiological angiogenesis, hence acting as a critical molecular brake on deregulated/ pathological angiogenesis. Loss of this brake, as seen in aggressive tumors such as basal-like breast cancer (32)(33)(34), can enable tumors to attain sustained angiogenesis (35), which is a hallmark of cancer (44). Overall, our results about Fringe are also consistent with experimental and theoretical observations that Fringe promotes lateral inhibition patterns (19,45) and are reminiscent of how asymmetric modifications of transmembrane ligand-receptor pairs can govern tissue-level pattern formation (46).…”
Section: Discussionsupporting
confidence: 79%
“…When many cells adopt this hybrid phenotype, the vasculature is expected to be quite chaotic: excessive number of small but poorly perfused vessels, resulting in pathological angiogenesis as observed during tumor growth (40). Therefore, our results offer a good unifying explanation for many experimental observations: (i) loss of Jagged significantly decreases vascular branching (14), (ii) loss of Delta leads to excessive nonproductive or poorly perfused angiogenesis (16), and (iii) loss of Fringe is correlated with increased MVD in tumors (35). Our results also attempt to resolve an apparent paradox between the canonical roles of Notch-Delta and Notch-Jagged signaling and the experimental observations about the overexpression of Delta and Jagged in angiogenesis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation